ADAPTASI PEREMPUAN TERPIDANA MEMBUNUH (LEMBAGA PERMASYAKATAN PEREMPUAN KELAS II A KOTA PEKANBARU) OLEH: SUCI WULANDARI - Wulandari, Suci; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The woman who had been convicted of murder should live his life in prison as an inmate, would need a way to adapt so that the inmates can their daily lives well in prison, inmates killing women must also try and sincerity in order to treat trauma cases entrap post. this phenomenon is interesting to examine the author; Adaptation Woman Convicted of Killing (Correctional Institution of Female Class II A Pekanbaru City), in the current study researchers interviewed four informants who are female convict the accused killed, informants were asked to tell the details again how chronological murder case that has ensnared them and what the motive accompanying , informants were also asked to tell his life after becoming prisoners Correctional Institution of Female Class II A Pekanbaru City. Using this theory, Robert K. Merton tries to explain deviations through social structures. According to this theory, social structures not only produce conformist behavior, but also produce deviant behavior. But in the explanation of this study, the author only uses conformity in which EM and SY informants are more related to this pattern, for MN informants more can be related to the adaptation of rebellion and retreatism related to cases that occur to YL informants, to connect adaptation to use by the informant according to the case that ensnared him. This study used qualitative methods and interviews were conducted in structured interviews where the research first prepared guidelines for interviews. Keywords: Women, Killing, Anomie